PERAN MEDIA PEMBELAJARAN DIGITAL DALAM MEMBENTUK PERKEMBANGAN KEPRIBADIAN SISWA DI PENDIDIKAN VOKASI - Ifan Hakim (CV. ADIBA AISHA AMIRA, 2025)
Vocational education requires the effective role of digital learning media in shaping student personality development. This study aims to analyze how the use of digital learning media can influence student personality development in vocational education. The results show that the use of digital learning media can increase student motivation, self-directed learning, and adaptability to change. Other positive impacts include eliminating spatial and temporal limitations, clarifying information, and reducing unnecessary costs. However, some challenges were found, such as not all schools having sufficient facilities and infrastructure to support learning processes using digital learning media. Therefore, this study recommends that the development of digital learning media should be tailored to student needs and abilities, considering existing limitations. In this way, digital learning media can become an effective tool in shaping student personality development in vocational education